Social Networks Sites: Usage and Effects - Ahmed Y. Abdelraheem (Sultan Qaboos University, 2013)
The aim of this paper is to explore the students' use of social networks sites (SNSs) and its effects on students' achievement. A questionnaire using a Liker type scale was distributed to a sample of 120 undergraduate students who participated in the study. The results show that students use SNSs for social matters more than for academic purposes. In this regard, there is no significant difference in the use of social network sites between female and male students. Students with smart mobile phones use SNSs more than those with normal mobiles. Facebook was the most used site. There is no significant difference in students' use of SNSs due to students GPA. More than fifty percent of sampled students spent two hours or more per day on SNSs. The study concludes with some recommendations.